PENGARUH PENDEKATAN PEMBELAJARAN STUDENT CENTERED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS XI DI MA BAHRUL ULUM KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Alvi Nugra Heni; Sarmidin Sarmidin; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Student Learning Center (SCL) is a learning approach that empowers students to be the center of attention during the learning process. However, based on preliminary observations made by the author at MA Bahrul Ulum Singingi especially in class XI in learning the Qur'an the Hadith found several symptoms as follows: 1. The teacher has used the student center learning approach, but when learning takes place students are not focused on participating in learning so that the results are not optimal. 2. SCL has been implemented in the Qur'anic Hadith lessons but there are still some students who have not experienced an increase in learning outcomes. 3. The teacher has no role to help students to solve problems when students experience difficulties in the learning process. The purpose of this study was to determine the effect of the student centered learning approach to student learning outcomes in Al-Qur'an Hadith class XI MA Bahrul Ulum Singingi District and the factors of the Student Centered Learning approach to student learning outcomes in Al-Qur'an subjects an Hadith class XI at MA Bahrul Ulum Singingi District Kuantan Singingi District. The research methodology is quantitative and is causal associative, namely research that aims to find the relationship between two or more variables about cause and effect on the variables that influence (independent variables) and variables that are influenced (dependent), namely Collecting data by means of Observation, Interview, and Questionnaire while data analysis uses IBM SPSS Statistics 24.0 The conclusion of this study is that there is a negative effect, this can be proven that the effect of student centered learning (Variable X) with learning outcomes (Variable Y) is said to have a negative effect on student learning outcomes The correlation coefficient is 2.3% Keywords: Student Centered Learning, Al-Qur'an Hadith, Learning Outcomes